Spatial choices of rats based on abstract visual information: Pattern- or configuration-discrimination? - Nekovářová, Tereza; Nedvídek, Jan; Bureš, Jan (Behavioural brain research, 2006)
Animals demonstrate their ability to represent a geometric configuration of their environment and to use this information for spatial decisions in their response space in many situations. In presented experiment, we examined the ability of rats to interpret a configuration of abstract visual stimuli to make spatial decisions in a real response space. We tested whether they are able to interpret spatial configuration of abstract stimuli or whether they perceive such visual stimuli simply as geometric patterns associated to particular spatial choices. The rats were tested in a Skinner box with four nosing holes in the transparent front wall through which a computer screen was visible. According to the visual stimuli on the screen, the rats should choose the appropriate nosing hole to obtain a reward. We compared two groups of rats: the first group was exposed to the visual stimuli designed as a representation of the response space: the position of rewarded nosing hole was shown in relation to other nosing holes. The second group was exposed to one of four geometric patterns associated to one of the four nosing holes but without any implicit information about the response space. The results suggested that rats using the stimuli with information about configuration were significantly more successful than rats trained to respond to visual stimuli unrelated to the geometry of the environment.
Keywords: Pattern Recognition, Visual; prostorové chování; výběrové chování; zraková percepce; financování organizované; Discrimination Learning; krysa rodu Rattus; Financing, Organized; zvířata; Visual Perception; Comprehension; Rats, Long-Evans; Choice Behavior; rozpoznávání obrazu; Male; potkani Long-Evans; Rats; diskriminační učení; Animals; Spatial Behavior; mužské pohlaví; pochopení